Can thermoregulation explain differences in habitat selection and distribution range in Calopteryx damselflies? - Laakso, Linda; Ilvonen, Jaakko J.; Suhonen, Jukka (Journal of thermal biology, 2025)
Body temperature is important for the behavioural and ecological performance of winged insects whose body temperature must exceed ambient temperature to fly. Although thermoregulation may affect geographical distribution and habitat selection of closely related species. The few studies that have been done on this subject have shown mixed results. Our aim was to study whether thermoregulation affects the coexistence of Calopteryx damselflies. We studied the body temperature of C. virgo and C. splendens under both field and laboratory conditions using an insect thermometer. These damselflies are ideal for studying thermoregulation, because they are closely related, but vary in colouration and size – factors that heavily influence insect thermoregulation. Results from our field and laboratory studies were consistent. Individual temperatures followed ambient temperatures linearly on a level ∼3 °C above it. C. virgo could maintain higher body temperatures than C. splendens. Individual body temperature at the activation, or the time before activation was not affected by species, sex or wing size. However, C. virgo warmed up faster than C. splendens in laboratory conditions. Thermoregulation may be a key factor explaining differences in geographical distribution, habitat preferences and behavioral differences between these species. The more melanized species C. virgo has a northern distribution range than less melanized C. splendens. Additionally, C. virgo inhabits shadier brooks and rivers whereas C. splendens prefers open and sunny habitats. C. virgo also wakes up earlier and is a more effective territorial contestant than C. splendens. These differences may partly be explained by their thermoecological differences. •Calopteryx body temperatures follow ambient temperatures (∼3 °C above it).•C. virgo could maintain slightly higher body temperatures than C. splendens.•Calopteryx activation temperature is not affected by species, sex or wing size.•C. virgo warms up faster and has a higher heating rate (°C/s) than C. splendens.•Thermoregulation may explain Calopteryx geographic range, habitat choice and behavior.